2007
DOI: 10.1002/edn.72
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing distress: the contribution of cognitive patterns to elevated distress among people with type 2 diabetes

Abstract: Background: While the prevalence of diabetes-related distress is now well recognised, less is known about how best we might intervene to reduce distress. Effective clinical interventions require a good understanding of the factors responsible for creating elevated distress about diabetes. At present there is a dearth of scientific information in this area. Aims: The aim of the present study was to identify cognitive patterns that may contribute to elevated distress among people with type 2 diabetes. It was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…This is consistent with the assumption that symptom appraisal is a key determinant of cognitive, emotional, and behavioural outcomes in the CSM of illness self-regulation (Leventhal, Cameron, Leventhal, & Ozakinci, 2005;Leventhal et al, 1984). These results concur with previous research highlighting the relationship between self-reported symptoms and diabetesrelated distress (Lange & Piette, 2006;Paddison et al, 2007;Paschalides et al, 2004), and are supported by a systematic review suggesting symptom experiences influence emotional responses to the diagnosis of diabetes (Thoolen et al, 2008).…”
Section: Evidence Of An Association Between Self-reported Diabetes Sysupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the assumption that symptom appraisal is a key determinant of cognitive, emotional, and behavioural outcomes in the CSM of illness self-regulation (Leventhal, Cameron, Leventhal, & Ozakinci, 2005;Leventhal et al, 1984). These results concur with previous research highlighting the relationship between self-reported symptoms and diabetesrelated distress (Lange & Piette, 2006;Paddison et al, 2007;Paschalides et al, 2004), and are supported by a systematic review suggesting symptom experiences influence emotional responses to the diagnosis of diabetes (Thoolen et al, 2008).…”
Section: Evidence Of An Association Between Self-reported Diabetes Sysupporting
confidence: 91%
“…The widely used common sense model (CSM) of illness self‐regulation (Leventhal, Diefenbach, & Leventhal, 1992; Leventhal, Nerenz, & Steele, 1984) identifies key illness‐related beliefs that are predicted to influence psychological health outcomes. For example, studies of people with established diabetes have shown that greater perceived consequences and higher self‐reported symptoms are associated with anxiety, depression (Paschalides et al , 2004), and diabetes‐related distress (Paddison, Alpass, & Stephens, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Younger age was linked to higher distress, which is consistent with other studies. 12,19,20 An unexpected diagnosis of diabetes at an early age and the lack of coping mechanisms in dealing with a debilitating chronic condition contribute to high distress levels. 20 Additional stressors are financial, family and work related.…”
Section: Discussionmentioning
confidence: 99%
“…12,19,20 An unexpected diagnosis of diabetes at an early age and the lack of coping mechanisms in dealing with a debilitating chronic condition contribute to high distress levels. 20 Additional stressors are financial, family and work related. 19 Health care providers should therefore take cognisance of the younger patient's needs for support in terms of accepting and coping with the emotional distress accompanying the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals with Type 2 diabetes, illness perceptions (beliefs) contribute as much as 34% to the variance in diabetes distress (Paddison & Alpass 2007). More specifically illness perceptions relating to diabetes consequences are associated with poorer emotional wellbeing (Hudson, Bundy, Coventry & Dickens 2014), and personal control mediates the relationship between diabetes distress and HbA1c (Gonzalez, Shreck, Psaros & Safren 2015).…”
Section: Introductionmentioning
confidence: 99%